The Increasing Acceptance of Onscreen Marking - the 'Tablet Computer' Effect - Coniam, David (Educational Technology ＆ Society, 2013)
This study extends recent investigations of onscreen marking (OSM) in the Hong Kong public examination context. It examines whether marker attitudes, which have shown increasing acceptance of OSM since it was first introduced in 2007, continue to develop this acceptance in a different context. In 2012, all pubic examinations were marked onscreen. While previous studies investigated the attitudes of mature markers marking extended essay answers for single subjects (English and Liberal Studies), the current study examines the attitudes and perceptions of much younger markers when marking short, objective answer questions in the 2012 Hong Kong Advanced Level Examination Use of English. In addition, because the markers were younger than usual, the issue of whether their attitudes to OSM were affected by the ownership of a tablet computer was also investigated. The findings, which have implications for other examination jurisdictions, indicate a growing acceptance of OSM, especially by tablet owners.